Catharanthus roseus extract mediated synthesis of cobalt nanoparticles: evaluation of antioxidant, antibacterial, hemolytic and catalytic activities. Issue 11 (1st November 2020) - Zaib, Maria; Shahzadi, Tayyaba; Muzammal, Irfa; Farooq, Umar
Abstract: In the recent work, synthesis of cobalt nanoparticles (CoNPs) was carried out by using whole plant extract of Catharanthus roseus . The average particle size of CoNPs calculated by XRD studies was found to be 27.08 nm. In assessment of antioxidant activity, DPPH radical scavenging percentage values of 37.05% and 79.19% were observed at 125 µg/ml and 1000 µg/ml nanoparticle concentration respectively. CoNPs exhibit greater growth inhibition percentage against gram negative bacteria in comparison to gram positive bacteria. In hemolytic assay, prepared nanoparticles depicted hemolysis rate of 1.53%. The surface of green synthesized CoNPs was modified with cetyltrimethylammonium bromide (CTAB) as a cationic surface modifier. Furthermore, the unmodified and modified CoNPs were studied for degradation of toxic alizarin red S dye in aqueous media. Best dye degradation results were observed at pH 6 with nanoparticle dosage of 10 mg and at lower concentration value of dye.